Industrial relations and working conditions developments in Europe 2011 - Curtarelli, Maurizio; Fric, Karel; Galli da Bino, Camilla; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2012)
This report describes the developments in industrial relations and working conditions in 2011 in the 27 EU Member States and Norway. It also considers EU-level industrial relations and working conditions with a focus on the economic situation and responses to it. In the past, Eurofound has analysed trends in working conditions and industrial relations in two separate reports. But due to the important interdependences between the two areas, we have combined developments in working conditions and industrial relations into a single annual report.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Hours of labor -- European Union countries; Industrial relations -- European Union countries; Working conditions -- European Union countries; European Union countries -- Social conditions; Electronic books